The Integration Of Multimedia Elements In Classroom Teaching Among TESL Teacher-Trainees - Puteh, Fatimah; Shukor, Siti Shuhaida (2010)
The integration of multimedia in classroom teaching has brought education into one step higher from the traditional technique or better known as “chalk and talk” teaching method to a more interactive and interesting teaching and learning process. The aim of this study is to investigate the extent to which multimedia is incorporated in classroom teaching among TESL teacher-trainees during the practical teaching. A total of 50 respondents consisting of third and fourth year TESL teacher-trainees from Universiti Teknologi Malaysia participated. This study also aims to find out whether or not the TESL teacher-trainees integrate multimedia in classroom teaching and if they do, the study aims to identify the multimedia elements they frequently use and if not, the study wants to find out the reasons for not integrating multimedia in their classroom teaching. Based on the result, it was reported that even among those who integrate multimedia, there are limitations to incorporate it in classroom teaching and this study has identified these limitations. Besides that, the benefits resulting from the integration of multimedia have also been identified. The result of the data analysis revealed four major findings namely the forms of multimedia incorporated in classroom teaching by TESL teacher-trainees,the benefits of the integrating multimedia in the classroom, the limitations, as well as the reasons for not integrating multimedia in classroom teaching during the practical teaching. Based on the findings, several conclusions and recommendations are drawn in order to improve the incorporation of multimedia in classroom teaching.